The mechanism of the gold loan and its use in the gold mining industry - V. T. Borisovich; Z. M. Nazarova; B. S. Madzhidov (Известия высших учебных заведений: Геология и разведка)
The essence of the gold loan and its role in the formation of the market of the precious metals have been considered. The gold mining companies are stated to be the main users of the borrowed gold. The main uses of the gold loans have been presented, including uses by gold mining companies, for the development of the mining industry and refinancing the debt. The modern problems of the functioning of the market for gold loans have been considered. The role of Central and commercial banks in the development of the market for gold loans has been reflected. The mechanism of the operation of the gold loan has been represented. The benefits of the gold credit for the gold mining industry compared to a conventional loan have been reflected.